2005
DOI: 10.1099/mic.0.27431-0
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the xenoestrogen nonylphenol by aquatic fungi and their laccases

Abstract: Degradation of technical nonylphenol (t-NP), known as an endocrine-disrupting compound mixture, was assessed, using the mitosporic fungal strain UHH 1-6-18-4 isolated from nonylphenol-contaminated river water, and a strain of the aquatic hyphomycete Clavariopsis aquatica. GC-MS analysis could resolve 12 peaks attributable to nonyl chain-branched t-NP isomers. All were degraded, to individual extents. Analysis of degradation metabolites suggested intracellular hydroxylation of the nonyl moieties of individual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 49 publications
2
114
0
3
Order By: Relevance
“…하지만, 수생환경에 잔류하는 난분해 성 물질의 제거 및 분해에 대한 연구는 대부분 수생식물을 이 용한 화학물질 흡착 및 수생 생태 환경의 복원에 대한 연구이 다 (Liao and Chang, 2004;Jayaweera and Kasturiarachchi, 2004). 하지만 nonylphenol의 생물학적 분해에 관하여서는 국 외에서도 nonylphenol 분해 미생물의 분리에 대한 보고만 되 어있는 정도이며 국내에서는 이에 대한 연구가 아직 이루어 지고 있지 않다 (Tanghe et al, 1999;Fujii et al, 2000;Fujii et al, 2001;Corvini et al, 2004;Junghanns et al, 2005;Shi and Bending, 2007 Table 2).…”
Section: 서 론unclassified
“…하지만, 수생환경에 잔류하는 난분해 성 물질의 제거 및 분해에 대한 연구는 대부분 수생식물을 이 용한 화학물질 흡착 및 수생 생태 환경의 복원에 대한 연구이 다 (Liao and Chang, 2004;Jayaweera and Kasturiarachchi, 2004). 하지만 nonylphenol의 생물학적 분해에 관하여서는 국 외에서도 nonylphenol 분해 미생물의 분리에 대한 보고만 되 어있는 정도이며 국내에서는 이에 대한 연구가 아직 이루어 지고 있지 않다 (Tanghe et al, 1999;Fujii et al, 2000;Fujii et al, 2001;Corvini et al, 2004;Junghanns et al, 2005;Shi and Bending, 2007 Table 2).…”
Section: 서 론unclassified
“…Proteomic studies of filamentous fungi have only recently begun to appear in the literature, despite the prevalence of these organisms in the fields of biotechnology, industry and environmental protection and their importance as both human and plant pathogens (Kim et al 2007;Doyle 2011;Bregar et al, 2012;Salvachúa et al 2013;Kroll et al 2014). Although the fungal biodegradation pathways of 4-NP have been proposed for several fungal organisms (Junghanns et al 2005;Gabriel et al 2008;Girlanda et al 2009;Różalska et al 2010;Krupiński et al 2013), little is known about the proteomic background of these processes. In the current work, the 4-n-NP biodegradation pathway in the filamentous fungus, Metarhizium robertsii, which leads to the complete removal of the xenobiotic through consecutive oxidations of the alkyl chain followed by aromatic ring oxidation and the initial proteome background of 4-n-NP removal, was described.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the abilities of selected fungi, including white rot fungi, to degrade this chemical, albeit to various extents (33). Extracellular oxidases (laccases) have been implicated in the fungal oxidation of NP (2,19).…”
mentioning
confidence: 99%